Personality traits and married woman's career choices. [article]. - Balmores, Rozel S.
The goal of the research was to establish whether personality traits affect the normative and non-normative career choice of women. Police work was considered as non- normative career choice while nursing was considered a normative career choice. Findings suggest significant differences between the personalities of policewomen and nurses.